2014
DOI: 10.20982/tqmp.10.2.p179
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry of taste: Methodological guide – from acquisition to data processing - and toolbox for MATLAB

Abstract: Abstract Abstract The food sensory science community has recently shown an increasing interest towards the measurement of emotions induced by product consumption. In this paper, we propose a standard method to objectively and quantitatively explore emotions in tasting situations through measurement and analysis of pupil diameter. Pupillometry is a well-known method for investigating cognitive load and emotional effects. However, since a standard method to analyze pupil response data is lacking, we provide here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 56 publications
1
32
0
2
Order By: Relevance
“…Because the size of the pupil is modulated by the autonomic nervous system, our results suggest that this system reacts differently to emotional and to neutral stimuli. This pattern of results confirms many studies suggesting that emotional intensity during picture viewing, sound auditioning, or tasting, is associated with high pupil dilation (Partala and Surakka, 2003;Bradley et al, 2008;Kret et al, 2013;Henderson et al, 2014;Lemercier et al, 2014). Bradley et al (2008) indicated that the dilation of pupil diameter covaried with other autonomic measures of intensity, such as the skin conductance, confirming that pupillary responses can be considered as a reliable index of emotional intensity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Because the size of the pupil is modulated by the autonomic nervous system, our results suggest that this system reacts differently to emotional and to neutral stimuli. This pattern of results confirms many studies suggesting that emotional intensity during picture viewing, sound auditioning, or tasting, is associated with high pupil dilation (Partala and Surakka, 2003;Bradley et al, 2008;Kret et al, 2013;Henderson et al, 2014;Lemercier et al, 2014). Bradley et al (2008) indicated that the dilation of pupil diameter covaried with other autonomic measures of intensity, such as the skin conductance, confirming that pupillary responses can be considered as a reliable index of emotional intensity.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, other studies suggest that non-visual emotions can also increase the diameter of pupils. This has been observed with participants listening to emotional sounds (Partala and Surakka, 2003;Babiker et al, 2013) or testing emotional products (Lemercier et al, 2014). In neuropsychology domain, by studying the effect of emotional stimuli on pupil diameter of people with Parkinson's disease, Dietz et al (2011) have found a normal sympathetic excitation to affective stimuli (indexed by pupil diameter), but no oculomotor differences.…”
Section: Touch and Emotional Developmentmentioning
confidence: 86%
“…The study included 60 participants, 31 men and 29 women. According to Lemercier et al (2014), previous pupillometry studies used varied numbers of participants (from 10 to 45, with an average of 24 and a median of 21 participants). Bojko and Adamczyk (2010) indicate that 30 participants can be considered sufficient for qualitative studies and for within-subjects ones with a large expected effect size, which is the case of this research.…”
Section: Methodsmentioning
confidence: 99%
“…(Laeng et al, 2012) Lielākā daļa empīrisko datu liecina, ka zīlītes diametrs mainās emocionālas slodzes rezultātā. (Lemercier et al, 2014) 1. att. Zīlītes diametrs atkarībā no apgaismojuma intensitātes.…”
Section: Pupilometrijaunclassified